2020
DOI: 10.3390/ijerph17238757
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of How Healthcare Organizations Can Support Hospital Nurses to Thrive at Work

Abstract: Background: Solutions that address the anticipated nursing shortage should focus on thriving at work: a positive psychological state characterized by a sense of vitality and learning, resulting in higher levels of work engagement, commitment, and wellbeing. Purpose: To synthesize international evidence on organizational factors that support hospital nurse wellbeing and to identify how the Social Embeddedness of Thriving at Work Model can support health managers to develop management approaches that enable nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 55 publications
2
50
0
5
Order By: Relevance
“…Data indicated that these barriers to accessing the support led to frustration from staff and potentially a sense that they were less valued by the organisation although this is not directly referenced. Whilst the authors acknowledge the difficulties of implementing individual support interventions so that they were geographically accessible to all, the potential impact on staff’s sense of being cared for or valued by their organisation is useful to understand as it has consequences for retention and staff wellbeing [ 30 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data indicated that these barriers to accessing the support led to frustration from staff and potentially a sense that they were less valued by the organisation although this is not directly referenced. Whilst the authors acknowledge the difficulties of implementing individual support interventions so that they were geographically accessible to all, the potential impact on staff’s sense of being cared for or valued by their organisation is useful to understand as it has consequences for retention and staff wellbeing [ 30 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thriving has also been found to be a mediator between structural and psychological empowerment together with personcentred care and climate (Silén et al, 2019). A conclusion from a review of thriving at work was that the model could guide managers towards creating a healthy nursing workforce (Moloney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the nurses at SMS of NHSL show a satisfactory level of Normative Commitment. Normative commitment refers to employees' feelings of obligation to their superiors, peers, subordinates, and other third parties to remain within the organization [20][21][22][23]. Therefore, in order to effectively motivate nurses to improve work commitment, intrinsic and extrinsic rewards should be made regularly so that the rigor to work hard is equally facilitated.…”
Section: Discussionmentioning
confidence: 99%